2012
DOI: 10.1016/j.jvs.2011.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Functional, morphologic, and molecular characterization of cold storage injury

Abstract: Long-term cold storage impairs vascular function, especially with respect to potassium signaling by calcium-dependent potassium channels. Microarray analysis confirmed impairment of pathways that are involved in calcium signaling and vascular function. Furthermore, various genes were significantly altered even after 2 hours, significantly before functional impairment was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…Considering that we recently reported that CS injury disrupts expression of certain mitochondrial proteins, it seemed reasonable that mitoBKα expression could be downregulated by CS [11]. Indeed, the expression of ion channels and other proteins can be rapidly regulated by temperature, and hypothermia can impact ion channel expression and activation [43][44][45]. However, in the present study, we found no evidence to suggest that CS + RW altered the expression of mitoBK channels.…”
Section: Nrk Cells Express Mitobk Channelscontrasting
confidence: 81%
“…Considering that we recently reported that CS injury disrupts expression of certain mitochondrial proteins, it seemed reasonable that mitoBKα expression could be downregulated by CS [11]. Indeed, the expression of ion channels and other proteins can be rapidly regulated by temperature, and hypothermia can impact ion channel expression and activation [43][44][45]. However, in the present study, we found no evidence to suggest that CS + RW altered the expression of mitoBK channels.…”
Section: Nrk Cells Express Mitobk Channelscontrasting
confidence: 81%
“…A few previous investigations could show endothelial dysfunction after in vitro hypoxia and reoxygenation [ 2 , 3 , 15 ], but it contradict the results from other studies showing no changes in the endothelium-dependent vasorelaxation induced by ACh [ 1 , 8 ]. It was also shown that prolonged (>1–2 days) cold storage is able to induce endothelial dysfunction [ 4 , 18 , 19 ]. In the present study we demonstrated a weak, but not significant reduction of the endothelium-dependent vasorelaxation in the vessels after 2h ischemic storage when compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Bradykinin induces an endothelium-dependent, nitric-oxide mediated vasodilatation [20]. This has been previously objectified by blunting the bradykinin-response with L-NMMA, an established blocker of the nitric oxide synthase [21]. The endothelium dependent vasodilatory functions were well preserved in blood-stored vessels but significantly impaired in NaCl-group.…”
Section: Discussionmentioning
confidence: 99%